2017
DOI: 10.1021/acs.biochem.7b01017
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Encoded Chemical Decaging in Living Bacteria

Abstract: We report the genetically encoded chemical decaging strategy for protein activation in living bacterial cells. In contrast to the metabolically labile photocaging groups inside Escherichia coli, our chemical decaging strategy that relies on the inverse electron-demand Diels-Alder (iDA) reaction is compatible with the intracellular environment of bacteria, which can be a general tool for gain-of-function study of a given protein in prokaryotic systems. By applying this strategy for in situ activation of the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 34 publications
0
31
0
1
Order By: Relevance
“…9,[13][14][15][16][17] These reactions are particularly useful for precision protein labeling, decaging, and cellular protein imaging. 13,14,[17][18][19][20][21][22][23][24] For example, tetrazine-containing amino acids have been genetically incorporated into proteins, allowing for a rapid bioorthogonal conjugation with trans-cyclooctene (TCO)labeled biomolecules. 13,17 Taking advantage of the high reaction rate and good biocompatibility of IEDDA reactions, Chen and others have redirected this reaction for sitespecific protein decaging.…”
Section: Graphical Abstractmentioning
confidence: 99%
“…9,[13][14][15][16][17] These reactions are particularly useful for precision protein labeling, decaging, and cellular protein imaging. 13,14,[17][18][19][20][21][22][23][24] For example, tetrazine-containing amino acids have been genetically incorporated into proteins, allowing for a rapid bioorthogonal conjugation with trans-cyclooctene (TCO)labeled biomolecules. 13,17 Taking advantage of the high reaction rate and good biocompatibility of IEDDA reactions, Chen and others have redirected this reaction for sitespecific protein decaging.…”
Section: Graphical Abstractmentioning
confidence: 99%
“…Subsequently, we analyzed whether deprotection with the prokaryote-compatible 3,6-dimethyl-tetrazine (26) could be used to switch on recombinant protein expression. 12,42 We found that 26 caused a minor delay on IPG (15) induced OVA expression without reducing overall expression levels ( Fig. S5 and Table S10 †).…”
Section: Resultsmentioning
confidence: 94%
“…Similarly, “Syn‐notch” receptors bear an antigen recognition domain and signal through the Notch pathway . Finally, a plethora of chimeric proteins have been engineered that combine fluorescent proteins with sensory domains and have been used to quantify endogenous small molecules . However, to the best of our knowledge, synthetic receptors have never been created by combining protein modules from GPCRs and RTKs.…”
Section: Figurementioning
confidence: 99%